Titanium oxide powder and its manufacturing method

A titanium oxide powder with controlled crystal ratios and nitrogen doping addresses the issues of UVA shielding and skin irritation, offering enhanced transparency and safety for cosmetic use.

JP7605980B2Active Publication Date: 2024-12-24TAYCA CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023522659
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-05-18
Filing Date
2022-05-16
Publication Date
2024-12-24
Estimated Expiration
2042-05-16

AI Technical Summary

Technical Problem

Existing titanium oxide powders used in cosmetics face challenges in achieving high UVA shielding effectiveness while maintaining transparency and safety, often causing bluish tint and skin irritation due to small particle sizes and aspect ratios.

Method used

The development of titanium oxide powder with a peak intensity ratio of anatase to rutile crystals less than 0.1, average short axis length between 10 to 50 nm, aspect ratio of 1 to 3, and nitrogen doping, along with a specific absorbance ratio and surface treatment, enhances UVA shielding and reduces skin irritation.

Benefits of technology

The resulting titanium oxide powder provides excellent UVA shielding, improved transparency, and reduced skin irritation, ensuring a good color tone and safety for cosmetic applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007605980000006
    Figure 0007605980000006
  • Figure 0007605980000007
    Figure 0007605980000007
  • Figure 0007605980000008
    Figure 0007605980000008
Patent Text Reader

Abstract

The present invention provides a titanium oxide powder wherein: the ratio (IA / IR) of the peak intensity (IA) of anatase crystals to the peak intensity (IR) of rutile crystals is 0.1 or less in X-ray diffractometry; with respect to grains contained therein, the average minor axis length is from 10 nm to 50 nm and the average aspect ratio is from 1 to 3; the ratio (A450 / A320) of the absorbance A450 at the wavelength of 450 nm to the absorbance A320 at the wavelength of 320 nm is from 0.015 to 0.5; nitrogen atoms are contained therein; and the peak associated with the nitrogen atoms is observed in the range from 395 eV to 402 eV in electron spectroscopy for chemical analysis (ESCA). Consequently, the present invention provides a titanium oxide powder which contains rutile crystals as the main component, and has an excellent UVA shielding effect and a good color, while being highly safe to the human body.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to titanium oxide powder, its uses, and its production method. [Background technology]

[0002] Sunscreen cosmetics are widely used because sunburn caused by ultraviolet rays has a negative effect on the skin. In addition to sunscreen cosmetics, makeup cosmetics are often required to have an ultraviolet shielding effect. In response to this, cosmetics containing inorganic particles such as titanium oxide and zinc oxide, and organic ultraviolet absorbers have been developed. Among them, titanium oxide is widely used because it has a high ultraviolet shielding effect and is less likely to cause skin troubles like organic ultraviolet absorbers. In particular, titanium oxide fine particles with a particle size of several tens of nm or less have excellent visible light transmittance because their dimensions are smaller than the wavelength of light, and cosmetics containing this have reduced whitishness derived from titanium oxide and have excellent transparency when used (see Patent Documents 1 to 3).

[0003] However, the finer and more highly dispersed the particles are to improve transparency, the more susceptible they are to Rayleigh scattering. The smaller the particles are, the stronger the Rayleigh scattering is, and blue light is more likely to be scattered than red light, so when cosmetics containing fine titanium dioxide particles are applied to the skin, a bluish tint is perceived. A pale color makes the skin look unhealthy, and is therefore undesirable for use in cosmetics.

[0004] One way to counter this is to add a small amount of iron oxide (Fe2O3) to neutralize the blue tint. However, iron oxide not only produces yellow, which is the complementary color of blue, but also red, so this inevitably results in a dull color in the cosmetic, and a better solution is desired.

[0005] Patent Document 4 describes a compound having a divalent sulfur atom (S 2-It is described that titanium oxide powder containing rutile crystals doped with rutile ions is obtained, which is said to cancel the blueness caused by Rayleigh scattering, and to have good transparency and color tone. It is also described that the particles contained in the titanium oxide powder have an average short axis length of 4 to 13 nm and an average aspect ratio of 2 to 7. Thus, by reducing the particle size, the transparency and the UVB (280 to 320 nm) shielding effect are improved, but the UVA (320 to 400 nm) shielding effect is reduced. In order to effectively suppress the deposition of melanin pigment due to sunburn and maintain white skin, it is necessary to improve the UVA shielding effect.

[0006] It is known that the UVA shielding effect is improved by increasing the particle size of titanium dioxide fine particles. However, as the particle size increases, there is a problem that the transparency decreases and the particles become whitish. In addition, spindle-shaped rutile titanium dioxide particles, which are widely used as titanium dioxide for UV shielding purposes, can be made larger in particle size by promoting crystal growth, but in this case, the crystals grow mainly in the long axis direction, so the aspect ratio (long axis length / short axis length) of the particles becomes large. In recent years, fine particles with a large aspect ratio are considered to have safety problems for the human body due to strong skin irritation, and for example, the European cosmetic standard specifies the aspect ratio of titanium dioxide fine particles to be 4.5 or less. Therefore, there are problems with simply growing the crystals to increase the particle size of titanium dioxide.

[0007] On the other hand, Non-Patent Document 1 describes a photocatalyst made of titanium oxide nanoparticles doped with nitrogen and containing both anatase and rutile crystals. It is shown that the titanium oxide nanoparticles absorb light of 400 to 500 nm (FIG. 4b). In addition, specific examples of the titanium oxide nanoparticles with a ratio of rutile crystals of 18.3%, 20.2%, and 36.9% are described, and it is described that the photocatalytic activity is the highest when the ratio is 20.2% (see Table 1 and FIG. 5). In other words, it is described that the photocatalytic activity is high when the ratio of anatase crystals is much higher than that of rutile crystals. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2010-173863 A [Patent Document 2] JP 2011-001199 A [Patent Document 3] JP 2014-084251 A [Patent Document 4] International Publication No. 2020 / 230812 [Non-patent literature]

[0009] [Non-Patent Document 1] J. Liu et al., Catalysts, 2020, 10, 1126 Summary of the Invention [Problem to be solved by the invention]

[0010] The present invention has been made to solve the above problems, and aims to provide a titanium oxide powder that is mainly composed of rutile crystals, has an excellent UVA shielding effect, is highly safe for the human body, and has a good color tone. Another aim is to provide a dispersion, particularly a cosmetic, that has good transparency and a good color tone. Another aim is to provide a suitable method for producing such a titanium oxide powder. [Means for solving the problem]

[0011] The above problem is due to the peak intensity (I R ) versus the peak intensity of anatase crystals (I A ) ratio (I A / I R ) is less than or equal to 0.1, The particles contained therein have an average minor axis length of 10 to 50 nm and an average aspect ratio of 1 to 3; Absorbance A at a wavelength of 450 nm 450 and absorbance A at a wavelength of 320 nm 320 Ratio to (A 450 / A 320 ) is 0.015 to 0.5, and The above-mentioned problems are solved by providing a titanium oxide powder which contains nitrogen atoms, and in ESCA (Electron Spectroscopy for Chemical Analysis) measurement, a peak derived from the nitrogen atoms is observed at 395 to 402 eV.

[0012] In this case, it is preferable that no peak of anatase type crystal is observed in the X-ray diffraction measurement. 2 It is also preferable that the absorbance A at a wavelength of 600 nm is 1 / g. 600 It is also preferable that L is 0.1 or less. * a * b * In the color system, L * The value is 92 to 99, and * Value is -5 to 2, b * A value of 3-30 is also preferred.

[0013] In a preferred embodiment, the surface of the particles contained in the powder is coated with a layer of an inorganic compound and / or an organic compound. In this case, the titanium oxide powder is formed by coating the surface of the particles with a layer of an inorganic compound, and the inorganic compound preferably contains at least one element selected from the group consisting of aluminum, magnesium, calcium, silicon, zinc, titanium, zirconium, iron, cerium, and tin. In this case, the titanium oxide powder is formed by coating the surface of the particles with a layer of an organic compound, and the organic compound is at least one selected from the group consisting of fatty acids or salts thereof, silicone compounds, coupling agents, and fluorine compounds. Furthermore, in this case, L * a * b * In the color system, L * The value is 92 to 99, and * Value is -5 to 2, b *A value of 2-30 is also preferred.

[0014] A preferred embodiment is a dispersion obtained by dispersing the titanium oxide powder in a dispersion medium. A preferred embodiment is also a cosmetic, paint, or ink containing the titanium oxide powder. A preferred embodiment is also a toner containing the titanium oxide powder as an external additive.

[0015] The above-mentioned problem is solved by an alkalinization step of adding an alkali metal hydroxide to an aqueous dispersion of hydrous titanium oxide to obtain an alkali metal titanate. an acidification step of adding hydrochloric acid to the aqueous dispersion of the alkali metal titanate to obtain titanium oxide containing rutile crystals; an impregnation step of impregnating the titanium oxide with a nitrogen-containing compound; and The above-mentioned problems can also be solved by providing a method for producing titanium oxide powder, which includes a calcination step at 200 to 600°C.

[0016] In this case, the specific surface area of ​​the titanium oxide before firing is 120 to 300 m 2 / g. It is also preferable that in the impregnation step, the hydrochloric acid remaining after the acidification step is neutralized with a basic nitrogen-containing compound, and the titanium oxide is impregnated with the nitrogen-containing compound. Effect of the Invention

[0017] The titanium oxide powder of the present invention is mainly composed of rutile crystals, has excellent UVA shielding effect, is highly safe for the human body, and has a good color tone. This makes it possible to eliminate the blueness caused by Rayleigh scattering, and to provide a dispersion, particularly a cosmetic, with good transparency and good color tone. Moreover, according to the manufacturing method of the present invention, such titanium oxide powder can be easily obtained. [Brief description of the drawings]

[0018] [Figure 1] 1 is a chart of an X-ray diffraction measurement of titanium oxide powder (after firing) having a specific surface area of ​​about 80 m2 / g obtained in Example 1. [Diagram 2]1 is an ESCA measurement chart of titanium oxide powder (after calcination) having a specific surface area of ​​about 80 m2 / g obtained in Example 1. [Diagram 3] 1 is an ESCA measurement chart of titanium oxide powder (after calcination) having a specific surface area of ​​about 60 m2 / g obtained in Example 1. [Figure 4] 1 is an ESCA measurement chart of titanium oxide powder "MT-100Z" used in Comparative Example 3. [Diagram 5] 1 is a transmission electron microscope (TEM) photograph of titanium oxide powder (after calcination) having a specific surface area of ​​approximately 80 m2 / g obtained in Example 1. [Figure 6] 1 is a transmission electron microscope (TEM) photograph of titanium oxide powder (after calcination) having a specific surface area of ​​approximately 60 m2 / g obtained in Example 1. [Figure 7] 1 is a graph comparing the absorbance of titanium oxide powders (after calcination) having a specific surface area of ​​approximately 80 m2 / g obtained in Example 1 and Comparative Example 2. [Figure 8] 1 is a graph comparing the light transmittance of the coating film of the emulsion preparations with a concentration of 10% by mass obtained in Example 1 and Comparative Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] The titanium oxide powder of the present invention has a rutile crystal peak intensity (I R ) versus the peak intensity of anatase crystals (I A ) ratio (I A / I R ) is less than or equal to 0.1, The particles contained therein have an average minor axis length of 10 to 50 nm and an average aspect ratio of 1 to 3; Absorbance A at a wavelength of 450 nm 450 and absorbance A at a wavelength of 320 nm 320 Ratio to (A 450 / A 320 ) is 0.015 to 0.5, and It contains nitrogen atoms, and a peak derived from the nitrogen atoms is observed at 395 to 402 eV in ESCA (Electron Spectroscopy for Chemical Analysis) measurement. Such titanium oxide powder was not able to be produced until the present inventors made extensive studies. It will be described in detail below.

[0020] In the titanium oxide powder of the present invention, the peak intensity of the rutile crystal in X-ray diffraction measurement (I R ) versus the peak intensity of anatase crystals (I A ) ratio (I A / I R ) is 0.1 or less. If the content of anatase crystals is high, the photocatalytic activity is high, and when used in applications where the material is exposed to ultraviolet or visible light, the organic matter that comes into contact with the titanium oxide particles is likely to deteriorate. In particular, when titanium oxide is blended into cosmetics, it is undesirable because it is likely to irritate the skin and cause problems.

[0021] Here, the peak intensity of the rutile crystal (I R ) is the peak intensity (I R ) The peak intensity of the anatase crystal (I A ) is the peak intensity (I A ) These peak intensities can be obtained using an X-ray diffraction apparatus described in the Examples of the present specification or an equivalent apparatus under the measurement conditions described in the Examples of the present specification or equivalent measurement conditions. Each peak appearing in the X-ray diffraction measurement chart does not need to be an independent peak, and an anatase crystal peak may be observed as a shoulder peak of a rutile crystal peak. The peaks are separated by analysis software attached to the apparatus, and the intensity of each peak is calculated.

[0022] Ratio (I A / I R) is preferably 0.05 or less, and more preferably, no peak of anatase crystals is observed in the X-ray diffraction measurement. Here, "no peak of anatase crystals is observed" means that no peak of anatase crystals is detected when the measurement is performed under the conditions described in the Examples of the present application. Under the conditions of this Example, the ratio (I A / I R ) is less than 0.03.

[0023] The average minor axis length of the particles contained in the titanium oxide powder of the present invention is 10 to 50 nm. When the average minor axis length is 10 nm or more, the shielding effect against UVA (320 to 400 nm) is improved. When the average minor axis length is less than 10 nm, the shielding effect against UVB (280 to 320 nm) is improved, but the shielding effect against UVA is reduced. It is important to shield UVB, which may cause inflammation in the skin, but it is also important to shield UVA, which causes melanin pigmentation and darkens the skin, and shielding UVA is particularly important from the viewpoint of beauty. The average minor axis length is preferably 12 nm or more, more preferably 14 nm or more. On the other hand, when the average minor axis length is 50 nm or less, the transparency of the coating film containing titanium oxide is improved. The average minor axis length is preferably 40 nm or less, more preferably 30 nm or less. The average minor axis length and the average major axis length are obtained by taking a transmission electron microscope (TEM) photograph and processing the image of the particles.

[0024] The particles contained in the titanium oxide powder of the present invention have an average aspect ratio (average major axis length / average minor axis length) of 1 to 3. In general, needle-shaped inorganic particles may irritate the lungs and skin, and therefore there are concerns about their safety to the human body. By making the average aspect ratio 3 or less, it is possible to improve safety to the human body. Furthermore, by making the average aspect ratio small, the feeling of squeaking characteristic of powders when applying a cosmetic material containing titanium oxide to the skin is significantly reduced, and the feeling of use is also excellent. It is more preferable that the average aspect ratio is 2.5 or less, and even more preferable that it is 2 or less.

[0025] The absorbance A of the titanium oxide powder of the present invention at a wavelength of 450 nm 450 and absorbance A at a wavelength of 320 nm 320 Ratio to (A 450 / A 320 ) is 0.015 to 0.5. 450 / A 320 By having a ratio (A) of 0.015 or more, blue light can be absorbed, effectively canceling out the blue color caused by Rayleigh scattering. Furthermore, the color tone becomes closer to the skin color, improving the sense of transparency when applied to the skin. 450 / A 320 ) is preferably 0.025 or more. 450 / A 320 If the ratio (A) exceeds 0.5, the coloring becomes too pronounced and it becomes difficult to use the composition in cosmetics. 450 / A 320 ) is preferably 0.4 or less, and more preferably 0.3 or less. The absorbance of titanium oxide powder is obtained by measuring the absorbance of a molded product obtained by compressing the powder using a spectrophotometer by a diffuse reflectance method.

[0026] The titanium oxide powder of the present invention contains nitrogen atoms, and in ESCA (Electron Spectroscopy for Chemical Analysis) measurement, a peak derived from the nitrogen atoms is observed at 395 to 402 eV. In ESCA measurement, it is said that the Ti-N bond energy peak appears at about 397 eV, and the Ti-NO and Ti-ON bond energy peaks appear at about 400 eV. The presence or absence of these peaks is judged based on whether or not the peaks are observed in ESCA measurement under the conditions described in the examples of the present application. In addition, if any of these peaks is observed, it is judged that the powder contains nitrogen atoms. It is known that in ESCA measurement, peaks derived from scandium atoms appear as a doublet peak (width 4.3 eV) at 406 eV and 401.7 eV. Of these, the 401.7 eV peak overlaps with the range of 395 to 402 eV specified in the present invention, but this peak is not considered. In addition, scandium atoms are not usually blended in the titanium oxide powder of the present invention.

[0027] As shown in FIG. 2, the specific surface area of ​​the sintered product obtained in Example 1 by neutralizing with ammonia and then calcining at 380° C. was approximately 80 m 2 In the case of titanium oxide powder with a specific surface area of ​​about 60 m / g, a peak is present on the surface of the particle and a peak is present inside the particle at about 397 eV. On the other hand, as shown in FIG. 3, the specific surface area of ​​the titanium oxide powder obtained by neutralizing with ammonia and then calcining at 480° C. in Example 1 is about 60 m 2 In the case of titanium oxide powder with a specific surface area of ​​100 nm / g, a peak is present on the surface of the particles at around 400 eV, but no peak is present in the interior of the particles at around 397 eV. This suggests that when particles are enlarged by firing at a higher temperature, the Ti-N bonds once formed inside the particles may disappear. On the other hand, as shown in FIG. 4, in the commercially available titanium oxide powder used in Comparative Example 3, which was not neutralized with ammonia or fired, no peak is observed in the range of 395 to 402 eV. In the case of titanium oxide particles obtained by firing without neutralization with ammonia, as in Comparative Example 2, the specific surface area of ​​Example 1 is about 60 m 2As with the titanium oxide powder of Example 1-4, a peak near 400 eV is present on the particle surface, but no peak near 397 eV is present inside the particle. This peak near 400 eV is believed to be due to nitrogen atoms derived from nitrogen molecules in the air bonding to the surface of the titanium oxide particles when fired in air. However, unlike the titanium oxide powders of Examples 1-4, the titanium oxide powder of Comparative Example 2 is unable to sufficiently absorb light at 450 nm, and the absorbance A at a wavelength of 450 nm is 450 and absorbance A at a wavelength of 320 nm 320 Ratio to (A 450 / A 320 ) is less than 0.015. From the above, it is presumed that even if the Ti-N bonds once formed inside the particles are lost by neutralizing with ammonia and then sintering at high temperature, some structure that absorbs light at 450 nm remains. Therefore, a peak due to nitrogen atoms is observed at 395 to 402 eV, and the ratio (A 450 / A 320 ) in the range of 0.015 to 0.5 makes it possible to obtain titanium oxide powder with a good color tone.

[0028] In addition, the absorbance A of the titanium oxide powder of the present invention at a wavelength of 600 nm 600 It is preferable that the absorbance A is 0.1 or less. 600 By keeping the absorbance A at 0.1 or less, it is possible to suppress the absorption of red light. If red light is absorbed in addition to blue light, the color tone becomes dull, which is undesirable when used as a cosmetic material. 600 is more preferably 0.07 or less, and even more preferably 0.05 or less.

[0029] The titanium oxide powder of the present invention, L * a * b * In the color system, L * The value is 92 to 99, and * Value is -5 to 2, b * The value is preferably 3 to 30. *A value of 92 or more makes it possible to obtain a powder with high whiteness without dullness. * The value is more preferably 93 or more, and even more preferably 95 or more. * A value of 2 or less suppresses redness. * The value is more preferably equal to or less than 0, and even more preferably equal to or less than −1. * A value of 3 or more effectively cancels out the blueness. * The value is more preferably 4 or more, and even more preferably 5 or more. * Values ​​above 30 may result in the yellow being too dark. * More preferably, the value is 20 or less, and even more preferably, the value is 15 or less.

[0030] In addition, the iron content of the titanium oxide powder of the present invention is preferably 300 ppm or less. The iron content (ppm) is the mass of iron element relative to the mass of the powder. By making the iron content 300 ppm or less, a dispersion, particularly a cosmetic, with excellent transparency without dullness can be obtained. The iron content is more preferably 200 ppm or less, and even more preferably 150 ppm or less. If the iron content is too high, the titanium oxide particles may aggregate, which may deteriorate the transparency. Note that the titanium oxide powders obtained in the present examples and comparative examples do not particularly contain iron element.

[0031] The titanium oxide powder of the present invention has a specific surface area of ​​25 to 100 m 2 / g. The specific surface area is preferably 25 m 2 By setting the specific surface area to 40 m / g or more, the whiteness is reduced, and a dispersion, particularly a cosmetic, having excellent transparency can be obtained. 2 / g or more, and more preferably 50m 2 / g or more. On the other hand, the specific surface area is 100m 2 By setting the specific surface area to 90 m / g or less, it is possible to obtain a dispersion, particularly a cosmetic, that can effectively block UVA and inhibit the production of melanin pigments due to sunburn. 2 / g or less.

[0032] The method for producing the titanium oxide powder of the present invention will be described below. A suitable production method includes an alkalinization step of adding an alkali metal hydroxide to an aqueous dispersion of hydrous titanium oxide (TiO2·nH2O) to obtain an alkali metal titanate, an acidification step of adding hydrochloric acid to the aqueous dispersion of the alkali metal titanate to obtain titanium oxide (TiO2) containing rutile crystals, an impregnation step of impregnating the titanium oxide with a nitrogen-containing compound, and a calcination step of calcining at 200 to 600°C.

[0033] In the alkalinization step, an alkali metal hydroxide is added to an aqueous dispersion of hydrous titanium oxide (titanium dioxide hydrate: TiO2·nH2O) to obtain an alkali metal titanate. The method for producing the hydrous titanium oxide used here is not particularly limited, but it is possible to use one produced by heating an aqueous solution of titanyl sulfate (TiOSO4) to hydrolyze it. The hydrous titanium oxide thus obtained usually contains anatase crystals.

[0034] Examples of the alkali metal hydroxide to be added to the aqueous dispersion of hydrous titanium oxide include sodium hydroxide, potassium hydroxide, and lithium hydroxide, with sodium hydroxide and potassium hydroxide being preferred, and sodium hydroxide being particularly preferred. The molar number of the alkali metal hydroxide added at this time is preferably 2 to 20 times the molar number of titanium element in the hydrous titanium oxide. The heating temperature at this time is preferably 60 to 120°C. This results in an aqueous dispersion of an alkali metal titanate. Examples of the alkali metal titanate include sodium titanate (Na2O7Ti3), potassium titanate, and lithium titanate.

[0035] In the acidification step following the alkalinization step, hydrochloric acid is added to the aqueous dispersion of the alkali metal titanate to obtain titanium oxide (TiO2) containing rutile crystals. By adding hydrochloric acid to make the aqueous dispersion acidic, an aqueous dispersion in which titanium oxide particles containing rutile crystals are dispersed can be obtained. The amount of hydrochloric acid added is an amount that can neutralize excess alkali in the aqueous dispersion and make the aqueous dispersion acidic. In addition, it is preferable to heat and age the mixture after adding hydrochloric acid, and the particles can be grown by adjusting the conditions. The preferred aging temperature is 40 to 110°C, more preferably 60°C or higher, and more preferably 105°C or lower. The preferred aging time is 2 minutes to 24 hours, more preferably 5 minutes or longer, and more preferably 10 hours or shorter.

[0036] In the impregnation step following the acidification step, the titanium oxide obtained is impregnated with a nitrogen-containing compound. The aqueous dispersion of titanium oxide obtained in the acidification step may be impregnated with a nitrogen-containing compound and then dried, or the aqueous dispersion may be dried and then impregnated with a nitrogen-containing compound. The nitrogen-containing compound used here is not particularly limited, and ammonia, ammonium bicarbonate, amines, urea, etc. may be used.

[0037] In the impregnation step, it is preferable to neutralize the hydrochloric acid remaining after the acidification step with a basic nitrogen-containing compound, and impregnate the titanium oxide with the nitrogen-containing compound. In this way, the nitrogen-containing compound can be uniformly impregnated into the aqueous dispersion containing titanium oxide particles at the same time as the neutralization operation. The basic nitrogen-containing compound used here can be ammonia, ammonium bicarbonate, amine, etc. Adding ammonia water is particularly preferable because it is easy to operate and inexpensive. After the neutralization operation, the titanium oxide particles are heated to remove moisture and dried. The suitable drying temperature is 70°C or higher and lower than 200°C. After drying, the titanium oxide powder (before firing) can be obtained by pulverizing or sieving as necessary.

[0038] In addition, the hydrochloric acid remaining after the acidification step can be neutralized with a base other than the nitrogen-containing compound. Examples of such bases include sodium hydroxide and potassium hydroxide. After the neutralization operation, the titanium oxide particles are heated to remove moisture and dried. A suitable drying temperature is 70°C or higher and lower than 200°C. After drying, the titanium oxide powder (before calcination) can be obtained by crushing or sieving as necessary. This titanium oxide powder (before calcination) can be impregnated with a solution, preferably an aqueous solution, of a basic nitrogen-containing compound and then subjected to a calcination step.

[0039] In the firing step, the titanium oxide powder is fired at 200 to 600°C. This can increase the minor axis length of the titanium oxide particles and reduce the aspect ratio. The firing temperature is preferably 250°C or higher, more preferably 300°C or higher. The firing temperature is preferably 550°C or lower, more preferably 500°C or lower. The atmosphere during firing is not particularly limited, and firing can be performed in an air atmosphere. In this case, nitrogen atoms derived from nitrogen molecules in the air may bond to the surface of the titanium oxide particles. After firing, pulverization or sieving can be performed as necessary to obtain titanium oxide powder (after firing).

[0040] The titanium oxide powder of the present invention can be used as it is for various applications, but it is preferable to coat the surface. That is, a preferred embodiment of the present invention is a titanium oxide powder in which the surfaces of titanium oxide particles contained in the powder are coated with a layer of an inorganic compound and / or an organic compound.

[0041] The inorganic compound for coating the titanium oxide particles is preferably one containing at least one element selected from the group consisting of aluminum, magnesium, calcium, silicon, zinc, titanium, zirconium, iron, cerium and tin. Coating with a compound containing these elements can improve the durability and dispersion stability of the titanium oxide particles. Particularly preferred is an aluminum compound, which is preferably coated in the form of aluminum hydroxide, thereby improving the dispersion stability and suppressing the photocatalytic activity specific to titanium oxide. Examples of the method for coating with aluminum hydroxide include a method in which a salt such as aluminum chloride is added to a slurry containing titanium oxide particles, and the salt is hydrolyzed to precipitate aluminum hydroxide on the titanium oxide particle surface. The preferred content of aluminum in the titanium oxide powder is 2 to 30 parts by mass in terms of Al2O3 per 100 parts by mass of TiO2.

[0042] The organic compound for coating the titanium oxide particles includes at least one selected from the group consisting of fatty acids or their salts, silicone compounds, coupling agents, and fluorine compounds. Among these, fatty acids or their salts are preferred, which can impart lipophilicity to the surface of titanium oxide particles and facilitate dispersion in an oil phase. In particular, when used as cosmetics, the cosmetics applied to the skin are less likely to be washed away by sweat or rain, improving durability. As the fatty acid used here, a higher fatty acid having 12 to 30 carbon atoms is preferably used, and as the salt thereof, an aluminum salt is preferably used. As a method for coating with fatty acids or their salts, a method in which an alkali metal fatty acid salt is added to a slurry containing titanium oxide particles, and then a strong acid such as sulfuric acid is added to precipitate the liberated fatty acid on the titanium oxide particle surface can be mentioned. The preferred content of fatty acid or its salt in the titanium oxide powder is 2 to 50 parts by mass relative to 100 parts by mass of TiO2. This content is the amount converted into the liberated fatty acid.

[0043] The layer of the inorganic compound covering the surface of the titanium oxide particles does not need to be a uniform layer, and may cover only a portion of the surface. The same applies to the layer of the organic compound. The layer of the inorganic compound and the layer of the organic compound may be formed as separate layers, or both the inorganic compound and the organic compound may be contained in one layer. In a preferred embodiment, the surface of the titanium oxide particles is covered with a layer containing aluminum hydroxide and a higher fatty acid having 12 to 30 carbon atoms or an aluminum salt thereof.

[0044] In the case of titanium oxide powder in which the surface of titanium oxide particles is coated with a layer of an inorganic compound and / or an organic compound, L * a * b * In the color system, L * The value is 92 to 99, and * Value is -5 to 2, b * The value is preferably 2 to 30. By coating the surface, the b * The value decreases, so for the coated titanium dioxide powder, * The preferred lower limit of the value has been lowered to 2. A more preferred range is L * Value, a * Value, b * Both values ​​are similar to those of uncoated titanium oxide powder.

[0045] A preferred embodiment is a dispersion obtained by dispersing the thus obtained titanium oxide powder of the present invention in a dispersion medium. The dispersion medium in this case may be water or an organic solvent. It may also be a mixed solvent of water and an organic solvent, or an emulsion formed from water and an organic solvent.

[0046] Suitable applications of the titanium oxide powder of the present invention include cosmetics, paints, inks, toners, etc.

[0047] Among these, the most suitable application is cosmetics, and it is preferably used as a cosmetic having an ultraviolet shielding effect, particularly as a cosmetic that can suppress the deposition of melanin pigment. The cosmetic of the present invention can be blended with inorganic pigments and organic pigments other than the titanium oxide powder of the present invention. Examples of inorganic pigments that can be used include titanium oxide, zinc oxide, red iron oxide, yellow iron oxide, black iron oxide, ultramarine, Prussian blue, cerium oxide, talc, muscovite, synthetic mica, phlogopite, biotite, synthetic fluorine phlogopite, titanium mica, micaceous iron oxide, sericite, zeolite, kaolin, bentonite, clay, silicic acid, silicic anhydride, magnesium silicate, aluminum silicate, calcium silicate, barium sulfate, magnesium sulfate, calcium sulfate, calcium carbonate, magnesium carbonate, boron nitride, bismuth oxychloride, alumina, zirconium oxide, magnesium oxide, chromium oxide, calamine, carbon black, hydroxyapatite, and complexes thereof. Usable organic pigments include silicone powder, polyurethane powder, cellulose powder, nylon powder, silk powder, polymethyl methacrylate (PMMA) powder, starch, polyethylene powder, polystyrene powder, tar dyes, natural dyes, and complexes thereof.

[0048] The cosmetic of the present invention may contain other ingredients depending on the purpose, such as pH adjusters, moisturizers, thickeners, surfactants, dispersion stabilizers, preservatives, antioxidants, sequestering agents, astringents, anti-inflammatory agents, UV absorbers, fragrances, etc.

[0049] The cosmetic of the present invention may be in the form of a milky lotion, lotion, oil, cream, paste, etc. Specific examples of its applications include makeup cosmetics such as sunscreen cosmetics, makeup base, foundation, concealer, control color, lipstick, lip balm, eye shadow, eyeliner, mascara, cheek color, and nail polish, as well as skin care cosmetics and hair care cosmetics.

[0050] When the titanium dioxide powder of the present invention is used in paints or inks, the titanium dioxide particles may be dispersed in a solution in which a base polymer is dissolved, or in an aqueous emulsion in which base polymer particles are dispersed. In addition, additives that are usually added to paints and inks, such as pigments, matting agents, surfactants, dispersion stabilizers, leveling agents, thickeners, antioxidants, and UV absorbers, can be blended. In addition, some paints containing fine titanium dioxide particles have a so-called "flip-flop" effect, in which the color tone changes depending on the viewing angle, but by using the titanium dioxide of the present invention, a "flip-flop" coating film with less blueness can be formed.

[0051] When the titanium oxide powder of the present invention is used as an external additive for a toner, it is mixed with toner particles containing a pigment. By using fine particles of titanium oxide, a toner having excellent stability of charging performance under various environments can be provided. In this case, various additives that are usually added can be blended into the toner. EXAMPLES

[0052] The present invention will now be described in more detail with reference to examples. The analytical and evaluation methods in the examples were as follows.

[0053] (1) X-ray diffraction measurement The titanium oxide powder was pressed flat against a sample holder using a glass plate and measured using an X-ray diffractometer (manufactured by Philips) under the following measurement conditions: ·Diffractometer system:XPERT-PRO ·Radiation source:CuKα Scan size: 2θ=0.008° Voltage: 45kV ·Current: 20mA Measurement range: 2θ=5~100° - Analysis software included: HighScore Plus

[0054] The peak intensity (I R ) and the peak intensity of anatase-type titanium dioxide (101 plane) at around 2θ = 25.3° (I A ) and measure their ratio (I A / I R ) was calculated. At this time, the peak search function of the above-mentioned attached software was used to perform a peak search under the following conditions. When a peak search was performed under these conditions, the ratio (I A / I R ) is 0.03. Therefore, the ratio (I A / I R ) is less than 0.03. ·Minimum significance: 0.50 Minimum peak tip: 0.10° Maximum peak tip: 1.00° Peak base width: 2.00° Method: Minimum of the second derivative

[0055] (2) ESCA measurement ESCA (Electron Spectroscopy for Chemical Analysis) measurements were performed using an X-ray photoelectron spectrometer (Shimadzu Corporation, "ESCA3400"). The powder sample was compressed into a thin film and then fixed with carbon tape for measurements. The distribution of nitrogen atoms in the depth direction of the sample was measured by repeatedly etching the surface by argon sputtering for 15 seconds. Correction was made using the C1s binding energy of 284.6 eV. The measurement and etching conditions were as follows:

[0056] (Measurement conditions) ·X-ray source: Mg-Kα ray Filament voltage-current: 12kV-15mA ·Vacuum degree: 1.0×10 -6 Less than Pa Measurement range: 385~415eV Measurement step: 0.1eV Number of times: 30 (Argon etching conditions) Filament voltage-current: 2kV-20mA Ion source: Argon gas Vacuum level during argon etching: 1.0×10 -4 Pa Etching time: 15 seconds / cycle

[0057] (3) Particle shape and size Transmission electron microscope (TEM) photographs were taken and the particles were image processed to determine the long axis length (nm) and short axis length (nm) of each particle. The aspect ratio is calculated by (long axis length / short axis length). More than 200 particles were measured to determine the average short axis length (nm) and average aspect ratio.

[0058] (4) Specific surface area The specific surface area was measured by the BET method using a fully automatic specific surface area measuring device (Macsorb HM model-1208 manufactured by Mountec Co., Ltd.) The measurement was performed after degassing for 20 minutes at 150° C. under a nitrogen gas atmosphere.

[0059] (5) Powder color An aluminum ring (43φ) for powder samples (manufactured by Rigaku Corporation, dimensions: outer diameter 43 mm, inner diameter 40 mm, height 5 mm) was set on the medicine wrapping paper, titanium oxide powder was filled into the ring and flattened, and the ring was pressed and molded at 15 MPa for 30 seconds using a tablet molding compression machine ("BRE-32" manufactured by Maekawa Test Machinery Manufacturing Co., Ltd.) to obtain tablets with a thickness of 2.5 to 3.0 mm, which were used as the measurement sample. The color of the sample thus obtained was measured using a color difference meter "CR-400" manufactured by Konica Minolta, Inc. After performing white calibration of the color difference meter, the L * a * b * L in color space * Value, a * value and b * The values ​​were measured.

[0060] (6) Absorbance The tablets obtained in the same manner as in "(5) Powder color" above were used as samples, and the absorbance was measured by the diffuse reflectance method using a spectrophotometer with an integrating sphere ("U-4100" manufactured by Hitachi High-Technologies Corporation). The measurement conditions were as follows. The measurement was performed after standard correction using a barium sulfate standard white plate. Scan speed: 300nm / min Sampling interval: 2nm ·Measurement wavelength: 250~700nm Absorbance A at a wavelength of 450 nm 450 and absorbance A at a wavelength of 320 nm 320 From the absorbance ratio (A 450 / A 320 ) was calculated.

[0061] (7) Color difference of coating film The PET film with a coating formed on a portion of its surface was placed on Bioskin (Biocolor BSC, Viewlux Co., Ltd.), a standard skin color, and the color difference was measured from the coating side using a colorimeter (CR-400, manufactured by Konica Minolta, Inc.). After performing white calibration of the colorimeter, the L * a * b * L in color space * Value, a * value and b * The color difference ΔE between the blank and the applied area was calculated using the average value of two measurements taken on the applied area, using the following formula. The smaller the ΔE value, the less deviation there is from the skin color, and the better the skin compatibility.

[0062]

number

[0063] Here, L * 1, a * 1 and b * 1 is blank L * Value, a * value and b * The value is L *2, a * 2 and b * 2 is the L of the application area * Value, a * value and b * Represents a value.

[0064] (8) Sensory evaluation of emulsion formulations (feel, whiteness, blueness, transparency) Ten panelists applied the emulsion formulation to the skin of their forearms in sunlight and evaluated the feel of the product while visually evaluating the whiteness, blueness, and transparency from different viewing angles. The blueness was evaluated by observing the areas where veins were visible through the skin.

[0065] Example 1 An aqueous solution of titanyl sulfate (TiOSO4) was heated to 100°C for hydrolysis, and titanium dioxide hydrate (TiO2·nH2O) was precipitated to obtain a slurry. The slurry was filtered and the resulting cake was washed with water to obtain 35 kg of titanium oxide hydrate cake (10 kg in terms of TiO2). The obtained titanium oxide hydrate contains anatase crystals. 70 kg of 48% by mass sodium hydroxide aqueous solution was added to the cake while stirring, and the mixture was heated and stirred at a temperature range of 95 to 105°C for 2 hours to obtain a slurry of sodium titanate (Na2O7Ti3). The slurry was filtered and the resulting cake was thoroughly washed with water to obtain a cake of sodium titanate. Water was added to the resulting cake to obtain a slurry containing 170 g / L of sodium titanate in terms of TiO2.

[0066] 14.0 kg of 35% by mass hydrochloric acid was added to the slurry containing sodium titanate, heated, and aged at 80°C for 10 minutes. The aged slurry was diluted with water to obtain a slurry containing titanium oxide at 70 g / L in terms of TiO2. The obtained titanium oxide contains rutile crystals. The titanium oxide slurry was heated to 80°C, adjusted to pH 7.0 with ammonia water, and aged for 30 minutes. After aging, the slurry was re-adjusted to pH 7.0 with ammonia water or hydrochloric acid, filtered and washed to obtain a titanium oxide cake. The cake was dried at 110°C, pulverized with an impact pulverizer, and passed through a 0.3 mm sieve to obtain titanium oxide powder (before calcination). The average minor axis length of this titanium oxide powder was 6 nm, and the average aspect ratio was 3.5. The specific surface area measured by the BET method was 204 m 2 / g, and L measured with a colorimeter * The value is 97.99, a * The value is -0.53, b * The value was 2.41. The above evaluation results are shown in Table 1.

[0067] The obtained titanium oxide powder (before calcination) was placed in a crucible with a lid that did not block air, and the powder was calcined in an air atmosphere using a box-type electric furnace ("KBF828N1" manufactured by Koyo Thermo Systems Co., Ltd.) until the specific surface area reached approximately 80 m 2 The resulting calcined product was sintered at 380°C for 120 minutes to obtain a specific surface area of ​​82.0 m / g. The sintered product was then crushed in an impact crusher and passed through a 0.3 mm sieve to obtain a specific surface area of ​​82.0 m. 2 / g of titanium oxide powder (after calcination). 2 By changing the calcination temperature to 480°C so that the specific surface area becomes 60.3 m 2 / g titanium oxide powder (after calcination) was also obtained.

[0068] The titanium oxide powder thus obtained (after calcination) was analyzed and evaluated according to the above-mentioned method. 2 The X-ray diffraction chart of titanium oxide powder (after calcination) with a molecular weight of 1.001 g / g is shown in Figure 1. No peaks of anatase crystals were detected, and the peak intensity (I R) versus the peak intensity of anatase crystals (I A ) ratio (I A / I R ) was less than 0.03. 2 In the X-ray diffraction measurement of the titanium oxide powder (after calcination) of 1000 g / g, no peak of anatase crystals was detected. Furthermore, in all of the titanium oxide powders (after calcination) obtained in Examples 2 to 4 and Comparative Examples 1 and 2 shown below, no peak of anatase crystals was detected.

[0069] Specific surface area is approximately 80m 2 The ESCA chart of titanium oxide powder (after calcination) with 1.0 μg / g is shown in Figure 2. Before etching (Ar-0 seconds), a peak was observed near the binding energy of 400 eV, and after etching for 15 and 30 seconds (Ar-15 seconds, Ar-30 seconds), a large peak near the binding energy of 397 eV and a small peak near 400 eV were observed. Both peaks were due to nitrogen atoms.

[0070] In addition, the specific surface area is approximately 60 m 2 The ESCA chart of titanium oxide powder (after calcination) with 0.1 g / g is shown in Figure 3. Before etching (Ar-0 seconds), a peak due to nitrogen atoms was observed near a binding energy of 400 eV, but after etching for 15 and 30 seconds (Ar-15 seconds, Ar-30 seconds), no peak was observed within the binding energy range of 395 to 402 eV.

[0071] Specific surface area is approximately 80m 2 A transmission electron microscope (TEM) photograph of the titanium oxide powder (after calcination) with a specific surface area of ​​about 60 m / g is shown in FIG. 5. The average minor axis length calculated by image processing based on the TEM photograph was 12.7 nm, and the average aspect ratio was 1.60. 2 A transmission electron microscope (TEM) photograph of the titanium oxide powder (after calcination) with a molecular weight of 1.0 μm / g is shown in Figure 6. The average minor axis length calculated by image processing based on the TEM photograph was 22.4 nm, and the average aspect ratio was 1.54.

[0072] The specific surface area measured by a colorimeter is approximately 80m 2 / g of titanium dioxide powder (after calcination) * The value is 96.04, a * The value is -1.66, b * The value was 7.93. The specific surface area was about 60 m 2 / g of titanium dioxide powder (after calcination) * The value is 96.58, a * The value is -1.37, b * The value was 7.58.

[0073] In addition, the specific surface area measured by a spectrophotometer was approximately 80 m 2 The graph of the absorbance of titanium oxide powder (after calcination) with a specific surface area of ​​about 80 m2 obtained in Comparative Example 2 is shown below. 2 The absorbance of the titanium oxide powder (after calcination) at 100 nm / g is also shown in Figure 7. The titanium oxide powder of Example 1 has a characteristic absorption near 450 nm, but the titanium oxide powder of Comparative Example 2, which was not neutralized with ammonia, did not have any absorption near 450 nm.

[0074] Specific surface area is approximately 80m 2 The absorbance of the titanium oxide powder (after calcination) of 1.02 g at 320 nm was 1.041, the absorbance at 450 nm was 0.088, and the absorbance at 600 nm was 0.014. 450 / A 320 ) was 0.085. In addition, the specific surface area was about 60 m 2 The absorbance of the titanium oxide powder (after calcination) of 1.025 g at 320 nm was 1.034, the absorbance at 450 nm was 0.081, and the absorbance at 600 nm was 0.007. 450 / A 320 ) was 0.078. The above evaluation results are based on the fact that the specific surface area is approximately 80 m 2 / g of titanium oxide powder (after calcination) is shown in Table 2. 2 The results of the titanium oxide powder (after calcination) and the amount of each powder are shown in Table 3.

[0075] (Preparation of lacquer varnish) The following materials were mixed uniformly to prepare 3,500 g of lacquer varnish. The solid content of nitrocellulose (NC) was 10% by mass. Nitrocellulose (H1 / 2): 500g (Kishida Chemical Co., Ltd., solid content: approx. 70% by weight) n-Butyl acetate: 1050g Ethyl acetate: 700g Ethylene glycol mono-n-butyl ether: 350g Toluene: 900g

[0076] (Preparation of Nitrocellulose Paint) The resulting lacquer varnish weighed 40 g, with a specific surface area of ​​approximately 80 m 2 1.714 g of titanium oxide powder (after calcination) with a molecular weight of 1.01 g / g and 130 g of φ0.5 mm zirconia beads (manufactured by Shinmaru Enterprises Co., Ltd.) as a dispersion medium were placed in a 100 mL bottle (J-bottle round wide mouth, manufactured by Nikko Hansen Co., Ltd.) and dispersed for 90 minutes with a paint conditioner (RED DEVIL "1400-OH"), after which the zirconia beads were separated to prepare a paint. The resulting paint contained 30 mass% titanium oxide relative to the total solid content.

[0077] (Formation and evaluation of nitrocellulose coating) The paint thus obtained was applied to a PET film (Panac Corporation: Lumirror 100T60) using an automatic bar coater equipped with a wire bar (No. 22), and dried at room temperature for 24 hours to form a coating film. The color difference ΔE between the formed coating film and Bioskin was evaluated according to the above method. The result was ΔE of 9.6. In addition, the specific surface area of ​​the coating film was approximately 60 m2. 2 When a paint and a coating were similarly prepared using titanium dioxide powder of 0.1 g / g and evaluated, the ΔE was 10.2.

[0078] (Surface treatment) Specific surface area is approximately 80m 2 / g or specific surface area of ​​about 60m 2Water was added to the titanium oxide powder (after calcination) of 70 g / L in terms of TiO2 to obtain a titanium oxide slurry of 70 g / L. The titanium oxide slurry was heated to 85°C and polyaluminum chloride (PAC: [Al3(OH) n Cl 6-n ] m A 10% aqueous solution of PAC was added and then aged for 10 minutes. The amount of PAC added was about 80 m 2 For 100 parts by mass of titanium oxide powder / g, 6 parts by mass of Al2O3 and a specific surface area of ​​approximately 60 m 2 The amount of Al2O3 was 4 parts by mass per 100 parts by mass of titanium oxide powder having a specific surface area of ​​about 80 m / g. The pH was adjusted to 6.0 using a 48% by mass aqueous solution of sodium hydroxide, and the mixture was aged for 30 minutes, after which sodium stearate was added. The amount of sodium stearate added was 1.0 g / g. 2 7 parts by mass per 100 parts by mass of titanium dioxide powder / g, specific surface area approximately 60 m 2 The amount was 5 parts by mass per 100 parts by mass of titanium oxide powder of 100% by mass / g. After adding sodium stearate and aging for 60 minutes, the pH was adjusted to 6.0 with 50% by mass sulfuric acid, and aging for another 30 minutes. The resulting slurry was filtered and washed with water to obtain a cake of titanium oxide coated with layers of aluminum hydroxide and stearic acid (or aluminum stearate). The cake was dried at 110°C, pulverized with an impact pulverizer, and passed through a 0.3 mm sieve to obtain a titanium oxide powder with a coated surface. The titanium oxide particles in the obtained powder were coated with layers of aluminum hydroxide and stearic acid (or aluminum stearate). The average minor axis length and average aspect ratio of the particles contained in the titanium oxide powder surface-treated in this way were almost the same as those of the titanium oxide powder before surface treatment.

[0079] The resulting surface coverage was approximately 80 m 2 / g and specific surface area of ​​approximately 60m 2 An emulsion preparation with a titanium oxide concentration of 25% by mass was prepared using titanium oxide powder of 0.1 g / g. 2Using titanium dioxide powder of 1000 g / g, emulsion preparations with a titanium dioxide concentration of 10 mass % were prepared. All emulsion preparations were intended for use as cosmetics.

[0080] (emulsion formulation with a concentration of 25% by mass) The oil phase raw material shown below weighs 30.87 g, and the surface coverage area is approximately 80 m 2 22.05g of titanium oxide powder with a molecular weight of 100g / g and 130g of φ0.5mm zirconia beads (manufactured by Shinmaru Enterprises Co., Ltd.) as a dispersion medium were placed in a 100mL bottle (manufactured by Nikko Hansen Co., Ltd.: J bottle round wide mouth), and dispersed for 5 hours with a paint conditioner (manufactured by RED DEVIL Co., Ltd., 1400-OH), after which the zirconia beads were separated to prepare an oil phase dispersion. 37.80g of this oil phase dispersion was placed in a 100mL polypropylene cup, and 25.2g of the mixture of water phase raw materials shown below was added while stirring at a stirring speed of 3000 rpm using a high-speed emulsifier / disperser ("TK Robomix" manufactured by Primix Corporation), and stirred at 3000 rpm for 5 minutes to prepare an emulsion formulation. (Oil phase raw material) Cyclopentasiloxane 21.07g: Shin-Etsu Chemical Co., Ltd. "KF-995" Liquid paraffin 4.9g: MORESCO White P-70 manufactured by MORESCO Corporation PEG-9 Dimethicone 4.9g: Shin-Etsu Chemical Co., Ltd. "KF-6019" (Aqueous phase raw material) 17.53g ion-exchanged water 1,3-butylene glycol 7.67g

[0081] The emulsion preparation thus obtained, with a concentration of 25% by mass, was applied to a PET film (Panac Corporation: Lumirror 100T60) using an automatic bar coater equipped with a wire bar (No. 6), and left to dry at room temperature for 24 hours to form a coating film. The color difference ΔE between the formed coating film and Bioskin was evaluated according to the above method. As a result, ΔE was 4.8. In addition, the specific surface area of ​​the surface covered was approximately 60 m2. 2When an emulsified preparation with a concentration of 25% by mass was similarly prepared using titanium oxide powder of 0.1 g / g and evaluated in the same manner, the ΔE was 6.4.

[0082] (10% by weight emulsion) 38.50 g of the oil phase raw material shown below, with a specific surface area of ​​approximately 60 m 2 8.75 g of titanium dioxide powder with a molecular weight of 1000 g / g and 130 g of φ0.5 mm zirconia beads (Shinmaru Enterprises Co., Ltd.) as a dispersion medium were placed in a 100 mL bottle (J Bottle, round, wide mouth, Nikko Hansen Co., Ltd.), and dispersed for 5 hours with a paint conditioner (RED DEVIL, 1400-OH), after which the zirconia beads were separated to prepare an oil phase dispersion. 37.80 g of this oil phase dispersion was placed in a 100 mL polypropylene cup, and 32.2 g of the mixture of water phase raw materials shown below was added while stirring at a stirring speed of 3000 rpm using a high-speed emulsifier / disperser (PRIMIX Corporation, "TK Robomix"), and stirred at 3000 rpm for 5 minutes to prepare an emulsion formulation. The viscosity of this emulsion formulation was measured using a B-type viscometer with a No. 2 rotor at 25 °C and 60 rpm, and was found to be 72 mPa·s. (Oil phase raw material) Dimethicone 29.75g: Shin-Etsu Chemical Co., Ltd. "KF-96L-1.5cs" Liquid paraffin 4.375g: MORESCO White P-70 manufactured by MORESCO Corporation PEG-9 polydimethylsiloxyethyl dimethicone 4.375g: Shin-Etsu Chemical Co., Ltd. "KF-6028P" (Aqueous phase raw material) 22.4g deionized water 1,3-butylene glycol 9.8g

[0083] The thus obtained emulsion preparation with a concentration of 10% by mass was applied to a PET film (Panax Corporation: Lumirror 100T60) using an automatic bar coater equipped with a wire bar (No. 6) to form a coating film. The color difference ΔE between this coating film and Bioskin immediately after application was measured according to the above method and was 6.4, but the color difference ΔE after leaving it to stand at room temperature for 24 hours and drying was 4.0. Here, in the emulsion preparation of Comparative Example 3 using commercially available titanium oxide powder, the color difference ΔE immediately after application was the same as that of the emulsion preparation of this Example, 6.4, but the color difference ΔE after drying was 4.4, which was larger than that of the emulsion preparation of this Example. From this, it was found that the emulsion preparation of this Example has improved transparency after drying compared to conventional products.

[0084] This emulsion formulation was applied to a polypropylene film (Mitsui Chemicals Tohcello Co., Ltd.: plain OPP sheet #40) using an automatic bar coater equipped with a wire bar (No. 6) to form a coating film. The light transmittance of this coating film was measured under the following conditions using a spectrophotometer (Hitachi High-Technologies Corporation "U-4100", using an integrating sphere). A graph plotting the transmittance against wavelength is shown in FIG. 8 together with the transmittance of the emulsion formulation of Comparative Example 3. It can be seen that the UVA (320 to 400 nm) shielding effect is greater than that of Comparative Example 3 using commercially available titanium oxide powder. In addition, the transmittance at 400 nm was 66.0%, the transmittance at 450 nm was 78.9%, and the wavelength at which the transmittance became 50% was 374 nm. Scan speed: 300nm / min Sampling interval: 2nm ·Measurement wavelength: 250~700nm

[0085] In addition, the usability, whiteness, blueness, and transparency of the obtained emulsion preparation were evaluated according to the above method, and a vote was made to determine whether the emulsion preparation of this example or the emulsion preparation of Comparative Example 3 using commercially available titanium oxide powder was superior. As a result, the emulsion preparation of this example has a lower viscosity than the emulsion preparation of Comparative Example 3, and the emulsion preparation spreads easily immediately after being dropped onto the skin, and the squeaky feeling specific to powder is greatly reduced, so all 10 panelists judged it to be a good usability. In addition, regarding the whiteness, blueness, and transparency after spreading and drying, all 10 panelists judged that the emulsion preparation using the titanium oxide powder of this example has less whiteness and blueness and has a more transparent feel.

[0086] Furthermore, in order to bring the viscosity of the emulsion preparation closer to that of the emulsion preparation of Comparative Example 3, an emulsion preparation with a concentration of 10% by mass was prepared in the same manner as above, except that the oil phase ingredients were changed as shown below. The viscosity after adjustment was measured using a B-type viscometer with a No. 3 rotor at 25°C and 60 rpm, and was found to be 1278 mPa s. (Oil phase raw material) Dimethicone 28.33g: Shin-Etsu Chemical Co., Ltd. "KF-96L-1.5cs" Liquid paraffin 4.375g: MORESCO White P-70 manufactured by MORESCO Corporation PEG-9 polydimethylsiloxyethyl dimethicone 4.375g: Shin-Etsu Chemical Co., Ltd. "KF-6028P" Aluminum stearate 1.42g

[0087] The emulsion formulation after viscosity adjustment was applied to a PMMA plate at 1.3 mg / cm 2 After applying an even amount of the product, it was allowed to dry naturally at room temperature for 30 minutes, and the SPF and UVAPF were measured using an SPF analyzer (Optometrics, Labsphere UV-2000S). The results showed that the SPF was 12.6, indicating that it effectively blocks UVB rays. The UVAPF was 4.7, indicating that it also effectively blocks UVA rays. The above evaluation results are summarized in Table 4.

[0088] Example 2 Titanium oxide powder was produced, analyzed and evaluated in the same manner as in Example 1, except that the slurry after the addition of hydrochloric acid was aged for 30 minutes at a temperature in the range of 100 to 105° C. The evaluation results are shown in Tables 1 to 3.

[0089] Example 3 Titanium oxide powder was produced, analyzed, and evaluated in the same manner as in Example 1, except that the slurry after the addition of hydrochloric acid was aged at 50° C. for 20 minutes. The evaluation results are shown in Tables 1 to 3. 2 For the titanium oxide powder (after calcination) of 0.1g / g, only the specific surface area was measured.

[0090] Comparative Example 1 Titanium oxide powder was produced, analyzed, and evaluated in the same manner as in Example 1, except that 10.0 kg of 35% by mass hydrochloric acid was added to the slurry containing sodium titanate, heated, and aged for 5 hours at a temperature in the range of 100 to 105° C. The evaluation results are summarized in Tables 1 to 3.

[0091] Comparative Example 2 This is an example in which the nitrogen-containing compound was not impregnated. 14.0 kg of 35% by mass hydrochloric acid was added to the slurry containing sodium titanate, and the mixture was heated and aged at 80° C. for 10 minutes. The aged slurry was diluted with water to obtain a slurry containing 70 g / L of titanium oxide in terms of TiO2. The obtained titanium oxide contains rutile crystals. The titanium oxide slurry was heated to 80° C., adjusted to pH 6.4 with a 24% by mass aqueous sodium hydroxide solution, and aged for 30 minutes. After the aging was completed, the slurry was re-adjusted to pH 6.4 with a 24% by mass aqueous sodium hydroxide solution or hydrochloric acid, filtered, and washed to obtain a titanium oxide cake. This cake was dried, crushed, and sieved in the same manner as in Example 1 to obtain titanium oxide powder (before firing). The subsequent steps were the same as in Example 1 to produce titanium oxide powder (after firing), which was then analyzed and evaluated. The evaluation results are summarized in Tables 1 to 3.

[0092] Example 4 This is an example in which ammonia water was sprayed immediately before calcination. A titanium oxide powder (after calcination) was produced in the same manner as in Comparative Example 2, except that 10 parts by mass of 24% by mass ammonia water was sprayed to 100 parts by mass of dried titanium oxide powder (before calcination) obtained in the same manner as in Comparative Example 2, and then analyzed and evaluated. The evaluation results are summarized in Tables 1 to 3.

[0093] Comparative Example 3 In the emulsion preparation with a concentration of 10% by mass produced in Example 1, a commercially available titanium oxide powder (manufactured by Teika Co., Ltd.: "MT-100Z") was used instead of the surface-coated titanium oxide powder used, and an emulsion preparation was prepared under the same conditions except that the dispersion time in the paint conditioner was set to 2 hours. "MT-100Z" is a titanium oxide powder containing spindle-shaped particles, with an average minor axis length of 7.9 nm and an average aspect ratio of 4.0, and was surface-treated with polyaluminum chloride and sodium stearate as in Example 1. The ESCA measurement chart of this powder is shown in FIG. 4. It can be seen that no peak is observed at 395 to 402 eV. The reason for shortening the dispersion time here is that the viscosity increased during dispersion, and the color difference ΔE between the coating film and Bioskin immediately after application was equivalent to that of the product of the present invention (6.4). The viscosity of this emulsion preparation was measured using a Brookfield viscometer with a No. 3 rotor at 25°C and 60 rpm, and was found to be 1492 mPa s. The resulting emulsion preparation was evaluated in the same manner as in Example 1, and the results are shown in Table 4.

[0094] [Table 1]

[0095] [Table 2]

[0096] [Table 3]

[0097]

Table 4

Claims

1. The peak intensity of the rutile crystal in the X-ray diffraction measurement (I R ) to the peak intensity of the anatase crystal (I A ) ratio (I A / I R ) is 0.1 or less, The particles contained therein have an average minor axis length of 10 to 50 nm and an average aspect ratio of 1 to 3; Absorbance A at a wavelength of 450 nm 450 and absorbance A at a wavelength of 320 nm 320 Ratio to (A 450 / A 320 ) is 0.015 to 0.5, and A titanium oxide powder containing nitrogen atoms, in which a peak derived from the nitrogen atoms is observed at 395 to 402 eV in ESCA (Electron Spectroscopy for Chemical Analysis) measurement.

2. 2. The titanium oxide powder according to claim 1, wherein no peak of anatase crystals is observed in the X-ray diffraction measurement.

3. Specific surface area is 25 to 100 m 2 The titanium oxide powder according to claim 1 or 2, wherein the titanium oxide powder has a molecular weight of 1000 or more and a molecular weight of 1000 or more.

4. Absorbance A at a wavelength of 600 nm 600 The titanium oxide powder according to claim 1 or 2, wherein the value is 0.1 or less.

5. L * a * b * In the color system, L * The value is 92 to 99, * The value is −5 to 2, and b * The titanium oxide powder according to claim 1 or 2, wherein the value is 3 to 30.

6. 3. The titanium oxide powder according to claim 1, wherein the surfaces of the particles contained in the powder are coated with a layer of an inorganic compound and / or an organic compound.

7. 7. The titanium oxide powder according to claim 6, wherein the surfaces of the particles are coated with a layer of an inorganic compound, and the inorganic compound contains at least one element selected from the group consisting of aluminum, magnesium, calcium, silicon, zinc, titanium, zirconium, iron, cerium, and tin.

8. 7. The titanium oxide powder according to claim 6, wherein the surfaces of the particles are coated with a layer of an organic compound, and the organic compound is at least one selected from the group consisting of fatty acids or salts thereof, silicone compounds, coupling agents, and fluorine compounds.

9. L * a * b * In the color system, L * The value is 92 to 99, * The value is −5 to 2, and b * The titanium oxide powder according to claim 6, wherein the value is 2 to 30.

10. 3. A dispersion obtained by dispersing the titanium oxide powder according to claim 1 or 2 in a dispersion medium.

11. A cosmetic comprising the titanium oxide powder according to claim 1 or 2.

12. A paint containing the titanium oxide powder according to claim 1 or 2.

13. 3. An ink containing the titanium oxide powder according to claim 1 or 2.

14. 3. A toner comprising the titanium oxide powder according to claim 1 or 2 as an external additive.

15. an alkalinizing step of adding an alkali metal hydroxide to the aqueous dispersion of hydrous titanium oxide to obtain an alkali metal titanate; an acidification step of adding hydrochloric acid to the aqueous dispersion of the alkali metal titanate to obtain titanium oxide containing rutile crystals; an impregnation step of impregnating the titanium oxide with a nitrogen-containing compound; and A firing step is performed at 200 to 600°C.

3. The method for producing titanium oxide powder according to claim 1, wherein the specific surface area of ​​the titanium oxide before calcination is 120 to 300 m 2 / g.

16. 16. The method for producing titanium oxide powder according to claim 15, wherein in the impregnation step, hydrochloric acid remaining after the acidification step is neutralized with a basic nitrogen-containing compound to impregnate titanium oxide with the nitrogen-containing compound.

Citation Information

Patent Citations

  • Preparation method of N-doped TiO2

    CN105858722A

  • Straw-bundled rutile-type titanium dioxide, cosmetics using the same and external additive for toner using the same

    JP2010173863A

  • Rutile-type titanium dioxide aggregated into bundle-shape and cosmetics using the same

    JP2011001199A

  • Rutile-type titanium oxide and cosmetic using the same

    JP2014084251A

  • Titanium oxide powder and method for manufacturing same

    WO2020230812A1